Mean Arterial Blood Pressures in the Intraoperative and Post-operative Setting Relative to Admission are Associated with Functional Outcome in Mechanical Thrombectomy. (16th November 2020) - Scullen, Tyler; Zeoli, Tyler; Carr, Christopher; Mathkour, Mansour H; Amenta, Peter S; Dumont, Aaron S; Nerva, John D
Abstract: INTRODUCTION: Perioperative care continues to advance with endovascular thrombectomy (EVT) in emergent treatment of acute ischemic stroke (AIS) caused by large vessel occlusion (LVO). Recent literature suggests control of perioperative blood pressure (BP) parameters critical in successful recanalization. METHODS: Patients treated at our comprehensive stroke center with EVT for AIS LVO from January 2015 to February 2020 were retrospectively reviewed (n = 335). Cases with dissection (n = 7), tandem occlusion(n = 42), or insufficient data (n = 12) were excluded. Systolic (SBP), diastolic (DBP), and mean arterial pressures (MAP) were collected from three time points: admission (aBP), intraoperative prior to recanalization (iBP), and within 24 hours post-operative (pBP). Outcome values of the NIHSS, mRS at discharge, and discharge dispositions were recorded. Percent difference of iBP and pBP relative to aBP was calculated and patients were categorized into one of three groups, where either both, one, or no parameters were within 10% of aBP. Analysis was carried out among the three groups. Good functional outcomes was defined as mRS < 3. RESULTS: A total of 274 patients were reviewed. No significant differences in admission, intraoperative, or post-operative MAP, SBP, or DBP, nor in patient mortality, or admission NIHSS were found between groups. Patients with both intraoperative and post-operative MAPs within 10% of admission MAP had a significantly higher increased association with good functional outcome as compared to other groups combined (49%v. 21%, P < . 0001). These patients also had significantly increased likelihood of home disposition (OR = 3.84, 95%, CI:1.98-7.43). CONCLUSION: Perioperative care for patients who undergo EVT for LVO is an evolving field. Strict perioperative BP regulation may impact odds of functional outcome. We report significant increases of good functional outcome and higher likelihood of home disposition in patients where intraoperative and post-operative MAPs did not deviate from 10% of admission MAP. Further studies are needed to clarify this relationship.